2021
DOI: 10.1021/acsaelm.1c00095
|View full text |Cite
|
Sign up to set email alerts
|

Stable Bioelectric Signal Acquisition Using an Enlarged Surface-Area Flexible Skin Electrode

Abstract: Numerous wearable devices were developed to measure bioelectric signals for continuous healthcare monitoring. The electrode, which interconnects electronics and the human body, significantly affects the signal quality. Although Ag/AgCl electrodes have been commonly used, noble-metal electrodes are more promising in terms of long-term reusability and flexibility. However, the signal-to-noise ratio (SNR) of noble metals is still insufficient for highly accurate biosignal acquisition. In this study, we propose an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 68 publications
0
30
0
Order By: Relevance
“…Yun et al used nanoscale gold particles to modify the surface of traditional metal electrodes and optimized the parameter settings of the nano-deposition process to increase the SNR of the electrode by increasing the specific surface area. The experimental results showed that the SNR increases by 51% in an ECG test and 63% in an EMG test [137]. Finally, through the quantitative detection of motion artifacts, it was found that the motion noise of the electrode was reduced by 95% compared with a traditional Ag/AgCl electrode [137].…”
Section: Manufacture Of Micro-nano Processing Technologymentioning
confidence: 94%
See 1 more Smart Citation
“…Yun et al used nanoscale gold particles to modify the surface of traditional metal electrodes and optimized the parameter settings of the nano-deposition process to increase the SNR of the electrode by increasing the specific surface area. The experimental results showed that the SNR increases by 51% in an ECG test and 63% in an EMG test [137]. Finally, through the quantitative detection of motion artifacts, it was found that the motion noise of the electrode was reduced by 95% compared with a traditional Ag/AgCl electrode [137].…”
Section: Manufacture Of Micro-nano Processing Technologymentioning
confidence: 94%
“…The experimental results showed that the SNR increases by 51% in an ECG test and 63% in an EMG test [137]. Finally, through the quantitative detection of motion artifacts, it was found that the motion noise of the electrode was reduced by 95% compared with a traditional Ag/AgCl electrode [137].…”
Section: Manufacture Of Micro-nano Processing Technologymentioning
confidence: 94%
“…Before placing the electrode, the following preparations should be made. At first, in order to ensure a good contact between the electrode and the skin, we should wipe the electrode with medical alcohol to remove the dead skin and oil on the skin surface and minimize the impedance between the electrodes [28]. en placing the electrode in the direction of the muscle fiber.…”
Section: E Placement Of Surface Electrodementioning
confidence: 99%
“…Wearable biomedical devices have received much attention to monitor individuals' health condition continuously by measuring various biosignals, such as electrocardiogram (ECG), electromyogram (EMG), ion concentration, and blood glucose level, in real time [1][2][3][4][5][6]. In order to design high-performance wearable devices, biosignal acquisitions with high signal-to-noise ratio (SNR) and sufficient sensitivity must be satisfied, as high-quality signals reduce the computational load for signal conditioning and increase the accuracy [7,8]. A sensing electrode is one of the essential components that affect the sensitivity of biosignal measurements.…”
Section: Introductionmentioning
confidence: 99%